2012
DOI: 10.1016/j.pain.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural alterations in migraine: A diffusion-weighted MRI study

Abstract: Migraine is a common and disabling neurological disease. The pathomechanism that underlies the disorder is not entirely understood, and reliable biomarkers are missing. In the current analysis we looked for microstructural alterations of the brain white matter in migraine patients by means of diffusion-weighted magnetic resonance imaging. The measurements were carried out with a novel approach based on fine-tuned nonlinear registration and nonparametric permutation test in an alignment-invariant tract represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 78 publications
11
102
1
1
Order By: Relevance
“…125,126,144,146 Diffusion weighted MRI studies showed that microstructural alterations of white matter, and thus of functional connectivity, are present across the orbitofrontal cortex, insula, thala mus and dorsal midbrain. 147 These alterations might reflect maladaptive plastic changes driven by dysrupted exo genous and endogeneous multimodal task process ing. 147 In another fMRI study, thalamic sensitization cor related with widespread mechanical allodynia during the migraine attack.…”
Section: Prospects For Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…125,126,144,146 Diffusion weighted MRI studies showed that microstructural alterations of white matter, and thus of functional connectivity, are present across the orbitofrontal cortex, insula, thala mus and dorsal midbrain. 147 These alterations might reflect maladaptive plastic changes driven by dysrupted exo genous and endogeneous multimodal task process ing. 147 In another fMRI study, thalamic sensitization cor related with widespread mechanical allodynia during the migraine attack.…”
Section: Prospects For Clinical Researchmentioning
confidence: 99%
“…147 These alterations might reflect maladaptive plastic changes driven by dysrupted exo genous and endogeneous multimodal task process ing. 147 In another fMRI study, thalamic sensitization cor related with widespread mechanical allodynia during the migraine attack. 148 Moreover, in a diffusion tensor MRI study, our research group found dynamic ictal and inter ictal microstructural variations in the thalamus that were related to the time since the last migraine attack, and seemed to mimic the cyclic neurophysiological changes described above.…”
Section: Prospects For Clinical Researchmentioning
confidence: 99%
“…Diffusion tensor imaging abnormalities have been found in a variety of chronic‐pain conditions, such as migraine (Szabó et al., 2012; Yu et al., 2013), temporomandibular disorder (Moayedi et al., 2012), and irritable bowel syndrome (Chen, Blankstein, Diamant, & Davis, 2011). Our current findings indicate that the white‐matter integrity in the chronic CRPS is widely affected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains unclear whether non-specific iron deposition plays a causative role in the development of migraine or is a consequence of repetitive attacks. DTI studies have reported both positive and negative results in terms of alterations of white matter structures in migraineurs [10,[15][16][17]22], which suggests that DTI changes are unlikely to characterize migraine. Therefore, our results of selective alterations in DKI metrics of the PAG represent a specific and pathognomonic imaging finding to evaluate patients with migraine.…”
Section: Discussionmentioning
confidence: 99%